Keberhasilan IB menggunakan semen beku hasil sexing dengan metode sedimentasi putih telur pada sapi PO cross - Erly Anna Rosita; Trinil Susilawati; Sri Wahyuningsih (Jurnal Ilmu-Ilmu Peternakan (Indonesian Journal of Animal Science), 2014)
The study was conducted in subdistrict Pakis, Malang Regency from May to July 2013. The study materials were 54 Ongole crossbred cattle. Twenty seven cattle were inseminated using non sexed semen (P0) and 27 cattle were inseminated using sexed semen (P1). Samples were selected randomly using criterion that semen deposition was in position 4+. Gestation evaluation was calculated based on non return rate (NRR), service per conception (S/C) and conception rate (CR). The study showed that P0 had 74% of NRR and P1 had 59% of NRR. S/C was found 1.37 at P0 and 1.48 at P1. CR was found 74% at P0 and 59% at P1. The study concluded that non sexed semen increased better gestation for Ongole crossbred cattle than sexed semen The study suggested that sexed semen remains able to be inseminated to those cattle with high attention on the sexing procedures.   Keywords: Sexing, egg white sedimentation methods, NRR, S/C, CR